Review of the deterministic modelling of deformation zones and fracture domains at the site proposed for a spent nuclear fuel repository, Sweden, and consequences of structural anisotropy - Stephens, M.; Follin, S.; Petersson, J.; Isaksson, H.; Juhlin, Christopher; Simeonov, A. (Elsevier, 2015)
© 2015 Elsevier B.V. This paper presents a review of the data sets and methodologies used to construct deterministic models for the spatial distribution of deformation zones and intervening fracture domains in 3-D space at Forsmark, Fennoscandian Shield, Sweden. These models formed part of the investigations to characterize this site, recently proposed as a repository for the storage of spent nuclear fuel in Sweden. The pronounced spatial variability in the distribution of bedrock structures, formed under ductile (lower amphibolite- or greenschist-facies) and subsequently brittle conditions, was controlled by two factors; firstly, the multiphase reactivation, around and after 1.8. Ga, of older ductile structures with a strong anisotropy formed under higher-temperature conditions at 1.87-1.86. Ga; and, secondly, by the release of rock stresses in connection with loading and unloading cycles, after 1.6. Ga. The spatial variability in bedrock structures is accompanied by a significant heterogeneity in the hydraulic flow properties, the most transmissive fractures being sub-horizontal or gently dipping. Although the bedrock structures at Forsmark are ancient features, the present-day aperture of fractures and their hydraulic tranmissivity are inferred to be influenced by the current stress state. It is apparent that the aperture of fractures can change throughout geological time as the stress field evolves. For this reason, the assessment of the long-term (up to 100,000. years) safety of a site for the storage of spent nuclear fuel in crystalline bedrock requires an evaluation of all fractures at the site, not only the currently open fractures that are connected and conductive to groundwater flow. This study also highlights the need for an integration of structural data from the ground surface and boreholes with magnetic field and seismic reflection data with high spatial resolution, during the characterization of structures at a possible site for the storage of spent nuclear fuel in crystalline bedrock.